Human Perfectibility. Kant and Fichte as Prophets of Moral Progress (2021)
This paper initially presents some references around the notion of moral progress, which generally point to the idea according to which it develops as a function of gradual improvement in humanity. Although such a statement encompasses a commonplace, the problem may be a more solid discussion, recognizing that progress is a reflection according to Kant, and it can also be a deduction from history on the part of Fichte. Thus, it seeks to expand the content in this regard, stating that, although these authors appeal to moral and theological scenarios to evaluate the future, in fact their interests are on the one hand the strengthening of the rule of law for the Fichtean case and for the Kantian perspective it would deal with institutions, which happens thanks to a human perfectibility.